ANALISIS SEMIOTIKA PADA LAGU DAERAH SUKU TOLAKI PEIA TAWA-TAWA - Wulandari, Kiki Reski (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
This research aims to analyze the semiotics of the Tolaki tribe's folk song "Peia Tawa-Tawa". The method in this research is to use library research with a qualitative approach. The results of the research show that the icon data is 2 data, the index is 3 data, and the symbol is 3 data. Based on the overall research results, it was concluded that the song is about happiness, togetherness, equality which is conveyed through the typical friendship dance of the Tolaki tribe, namely the Lulo Dance. Keywords : semiotics, folk song, tolakinese tribe, peia tawa-tawa